Effectiveness of chemotherapy counselling on self-esteem and psychological effects among cancer patients in Malaysia: randomized controlled trial - Mohd Sidik, Sherina; Zavare, Mehrnoosh Akhtari; Periasamy, Ummavathy; Gyanchand Rampal, Lekhraj Rampal; Ismail, Siti Irma Fadhilah; Mahmud, Rozi (Elsevier, 2018)
Objectives: The aim of this study was to implement and evaluate the outcomes of chemotherapy counselling based on the "Managing Patients on Chemotherapy" module on self-esteem and psychological affect (anxiety, depression) of cancer patients by pharmacists in ten selected government hospitals in Peninsular Malaysia. Methods: A randomized control trial was conducted among 2120 cancer patients from April 2016 to January 2017 in ten selected government hospitals in Peninsular Malaysia. Cancer patients were randomly assigned to intervention and control groups. The intervention group received chemotherapy counselling by pharmacists based on the "Managing Patients on Chemotherapy" module. The outcomes were assessed at baseline, 1st, 2nd and 3rd follow-ups after counselling. In the course of data analysis; independent sample t-test, chi-square and two-way repeated measures ANOVA were conducted. Results: Mean scores of self-esteem in the intervention group had significant difference in comparison with those of the control group in the 1st, 2nd and 3rd follow-ups after counselling (P < 0.0001). Also, among those with depression and anxiety at baseline, there was reduction in depression and anxiety scores after the 1st, 2nd and 3rd follow-ups after counselling (p < 0.05). Conclusion: Repetitive counselling by pharmacists based on the "Managing Patients on Chemotherapy" module had positive effect on improving self-esteem and psychological affect of cancer patients undergoing chemotherapy in Peninsular Malaysia. Practice implications: This module can be used for all Malaysian cancer patients undergoing chemotherapy to improving self-esteem and psychological affect.